Four-rod technique for stabilization of lumbar spine in a case of spine metastases - Tharmaseelan, Shival; Lim, Teck Siang; Harun, Mohd Hezery; Ramlee, Fadzrul Abbas (Lycia Press London UK, 2024)
Objective: The occurrence of spine metastases often indicates disseminated disease and portends a short-term prognosis in cancer patients. This study discusses the challenges in the surgical management of spinal metastases and evaluates the effectiveness of a 'Four-rod' technique in a patient with disseminated renal cell carcinoma. Case: A 40-year-old male with renal cell carcinoma and metastases presented with severe lower back pain and instability due to extensive vertebral destruction. Despite the poor prognosis, a 'Four-rod' construct was employed to stabilize the spine. Post-surgery, the patient experienced significant pain reduction and improved mobility. Conclusion: The 'Four-rod' technique minimized complications such as pseudoarthrosis and implant failure. It proved effective in stabilizing the spine without increasing operative time or blood loss, thereby enhancing the patient's quality of life. This study underscores the importance of addressing spinal instability in patients with metastatic disease and suggests that multiple-rod constructs may offer superior outcomes.